Peaches phenology and production submitted to foliar nitrogen fertilizer and calcium nitrate - Ferreira, Rafael Bibiano [UNESP]; Leonel, Sarita [UNESP]; Souza, Jackson Mirellys Azevêdo [UNESP]; Silva, Marcelo de Souza [UNESP]; Ferraz, Rafael Augusto; Martins, Rafaelly Calsavara [UNESP]; da SILVA, Marcela Sant’Anna Cordeiro (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2019)
Choosing cultivars that require less chilling temperatures to overcome dormancy is crucial, for example, peaches that grow in subtropical areas, which is not an appropriate climate for them. Thus, alternative techniques are necessary to induce sprouting. Yet there are not many available products in market, restricting options for fruit growers to a reduced number of chemical molecules, which are often harm the health to applicators. Therefore, this study aimed to assess phenological cycles and productive performance of three peach cultivars, submitted to foliar nitrogen fertilizer and calcium nitrate to induce sprouting. This study took place at Experimental Orchard of School of Agriculture (FCA, UNESP), Botucatu, state of São Paulo. Three peach cultivars were evaluated: ‘Douradão’, ‘BRS Kampai’ and ‘BRS Rubimel’ by applying four doses of foliar nitrogen fertilizer (FNF) at 0, 1.25, 2.50 and 3.75%; associated with 4% calcium nitrate. A 3x4 factorial arrangement (3 cultivars X 4 FNF doses) in a randomized block design was used, with 4 replicates and 2 plants per plot, totalizing 96 plants. Results indicated that FNF positively affected cultivars development, providing wider sprouting, flowering and fruit set; consequently, greater production. Then FNF became a good alternative to induce sprouting in peaches at mild winter temperatures. Moreover, ‘BRS Rubimel’ presented high sowing percentage associated with low flowering and fruit set percentages, that is, low production mainly caused by its lack of adaptability to studied region.
Fenologia e produção de pessegueiros submetidos à aplicação de fertilizante foliar nitrogenado e nitrato de cálcio
Keywords: Erger; Overcoming dormancy; Prunus persica (L.) Batsch; Sprout induction